2012
DOI: 10.1039/c2cs35068h
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of polyacetylenes and cyanopolyacetylenes in Titan's atmosphere and their role in astrobiology

Abstract: This tutorial review compiles recent experimental and theoretical studies on the formation of polyacetylenes (H(C≡C)(n)H) and cyanopolyacetylenes (H(C≡C)(n)CN) together with their methyl-substituted counterparts (CH(3)(C≡C)(n)H, CH(3)(C≡C)(n)CN) as probed under single collision conditions in crossed beam studies via the elementary reactions of ethynyl (CCH) and cyano radicals (CN) with unsaturated hydrocarbons. The role of these key reaction classes in the chemical evolution of Titan's orange-brownish haze lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 105 publications
1
45
0
Order By: Relevance
“…Moreover, since the investigated polymer chains could form helical conformations, as justified in earlier studies, 66-68 the polymers 25 obtained by emulsion polymerization were further explored for elucidating the secondary structures of the polymer chains. Both CD (circular dichroism) and UV-vis absorption spectra demonstrated that in all the four polymer particles obtained via emulsion polymerization approach, the polymer chains adopted 30 helical structures, just as expected. It is further found that the emulsion polymerization, when compared to the corresponding solution polymerization, is much more beneficial for the polymer chains to take helical conformations with predominantly onehanded helicity.…”
Section: Emulsion Polymerizationssupporting
confidence: 67%
See 4 more Smart Citations
“…Moreover, since the investigated polymer chains could form helical conformations, as justified in earlier studies, 66-68 the polymers 25 obtained by emulsion polymerization were further explored for elucidating the secondary structures of the polymer chains. Both CD (circular dichroism) and UV-vis absorption spectra demonstrated that in all the four polymer particles obtained via emulsion polymerization approach, the polymer chains adopted 30 helical structures, just as expected. It is further found that the emulsion polymerization, when compared to the corresponding solution polymerization, is much more beneficial for the polymer chains to take helical conformations with predominantly onehanded helicity.…”
Section: Emulsion Polymerizationssupporting
confidence: 67%
“…In the first case, successfully utilized heterophase polymerization methods include emulsion, suspension, precipitation, and dispersion polymerization techniques and the respective derivatives. Among the methods, emulsion 30 polymerization techniques seem to be the most widely used one. In the second case, i.e.…”
Section: Preparation Of Acetylenic Polymer Particlesmentioning
confidence: 99%
See 3 more Smart Citations